EPR spectroscopic investigation of radical-induced degradation of partially fluorinated aromatic model compounds for fuel cell membranes - Schönberger, Frank; Kerres, Jochen; Dilger, Herbert; Roduner, Emil (Physical chemistry chemical physics : PCCP, 2009)
EPR spectroscopic investigations of reactions between monomeric model compounds representing typical structural moieties of poly(aryl) ionomers and photochemically generated hydroxyl radicals are reported. Deoxygenated solutions of the model compounds (in a water/methanol mixture) containing hydrogen peroxide at defined pH values were exposed to UV light in the flow cell within the cavity of an EPR spectrometer. Spectra were analyzed by computer simulation and the formed radicals were assigned by comparing their g-factors and hyperfine coupling constants (hfccs) with those from the literature and from density functional theory (DFT) calculations. The relevance for polymer electrolyte membrane fuel cells (PEMFCs) and alkaline-anion exchange membrane fuel cells (AAEMFCs) is discussed.